Comparative Study Of Android-Based Learning Media With Web-Based Learning Media - Monica Fransisca; Renny Permata Saputri (The Indonesian Journal of Computer Science, 2024)
Many choices of learning media were available, so it’s necessary to research which learning media are appropriate and suit the needs. Learning media are now technology-based, for example android-based and web-based learning media. The use of these two media was similar and widely used, so it’s necessary to examine the comparison of effectiveness. To conduct this research, a comparative analysis method with a literature study approach was used. Through the analysis, a comparison was carried out by comparing several research relevant with the themes. The research focuses on the level of effectiveness. The comparison of this research that comes from the research team itself, and several other studies. Based on comparison, the results showed that android-based learning media had a higher effectiveness percentage, 87.67%, while web-based learning media had average 80.39%. The conclusion of the research was that android-based learning media has a higher effectiveness compared to web-based learning media.